English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i need it quick

2007-03-12 05:15:52 · 4 answers · asked by marinehacker202 2 in Science & Mathematics Mathematics

4 answers

1/sinx - cosx [cosx/sinx] =

1/sinx - cos^2x/sinx =

[1 - cos^2x] / sinx =

sin^2x / sinx =

sinx

2007-03-12 05:18:40 · answer #1 · answered by Anonymous · 0 0

csc(x) - cos(x)cot(x) = sin(x)
1/sin(x) -cos(x) cos(x)/sin(x) =sin(x)
Multiply by sin(x), getting:
1 -cos^2(x) = sin^2(x)
1= sin^2(x) + cos^2(x)
1 = 1

2007-03-12 05:23:00 · answer #2 · answered by ironduke8159 7 · 0 0

csc(x) - cos(x)cot(x) = sin(x)
1/sin x-cos^2 x/sin x=sin x
(1-cos^2 x)/sin x=sin x
sin^2 x /sin x=sin x
sin x= sin x

2007-03-12 05:20:37 · answer #3 · answered by yupchagee 7 · 0 1

1/sin(x)-cos^2(x)/sin(x)
1-cos^2(x)/sin(x)
1-co^2(x)=sin^2(x)
sin^2(x)/sin(x)
sin(x)

2007-03-12 05:21:41 · answer #4 · answered by miinii 3 · 0 0

fedest.com, questions and answers